PENGARUH BAP TERHADAP PEMBENTUKAN DAN PEMBESARAN UMBI MIKRO KENTANG KULTIVAR GRANOLA - Danner Sagala; Herman Wafom Tubur; Uma Fatkhul Jannah; Chea Sinath (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2012)
The experiment was aimed to know the effect of BAP Plant Regulator to the formation and the development of Potato’s Micro Tuber. The treatment were 0; 2,5; 5; 7,5 mg/L BAP. The growing media was Murashige and Skoog (MS0). The result showed that BAP did not significantly affected the number, diameter, wet and dry weight of the tuber. However, the highest of number, diameter, wet and dry weight was found at the 7,5 mg/L BAP. The fastest formation of tuber was yielded in 5 mg/L BAP.